Sustainable agrivoltaic system for food and energy sector in Bangladesh (Bangladesh Journal of Scientific and Industrial Research, 2023)
In South Asia, agriculture heavily relies on groundwater for irrigation. The withdrawal is nearly 250 km3 annually. Approximately, 12 million electric and 10 million diesel water extraction pumps, totaling about 22 million, are in use in this area. In contrast, while PV-powered solar irrigation pumps are becoming more popular, they take up agricultural land, increasing the competition for land resources between food and clean energy production. It is left unattended during the off-season, wasting a lot of potential solar power that could produce green electricity. To address this, an integrated farming model can be established, utilizing existing solar pump facilities for crop cultivation, rearing Black Bengal Goats, and native fish farming. This diversified approach combines sustainable energy solutions with solar irrigation, generating both agricultural products and electricity while maintaining agricultural land for cultivation and promotion of clean energy production. The proposed method has produced both agricultural products and electricity simultaneously. This integrated system offers a solution to the challenges faced in the region, balancing food production and clean energy goals effectively.Bangladesh J. Sci. Ind. Res. 58(3), 163-172, 2023